2010
DOI: 10.1597/09-070
|View full text |Cite
|
Sign up to set email alerts
|

MRI for Definitive In Utero Diagnosis of Cleft Palate: A Useful Adjunct to Antenatal Care?

Abstract: Fetal MRI enables us to predict accurately the extent of a cleft palate after an ultrasound diagnosis of cleft lip. With more accurate diagnosis of the severity of the cleft, we can counsel patients more precisely and plan postnatal management correctly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 24 publications
(22 reference statements)
2
51
0
Order By: Relevance
“…However, the accuracy of US in the present study was higher than in previous studies. In those, MRI had obvious advantages over US . Interestingly, Dabadie et al reported that the US and MRI results were consistent in 91% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, the accuracy of US in the present study was higher than in previous studies. In those, MRI had obvious advantages over US . Interestingly, Dabadie et al reported that the US and MRI results were consistent in 91% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the technique, the limitations include diffi culty in visualising skeletal components and fetal movement. Although echoplanar imaging sequences have been proposed for studying skeletal structures, in our study, they were unable to provide additional informa- [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…These advantages therefore enable better treatment planning in the setting of multidisciplinary patient management [28][29][30].…”
Section: Conclusionimentioning
confidence: 99%
“…8 In high-risk populations (i.e. 10 9 Antenatal MRI offers no particular advantage over ultrasound for the diagnosis of cleft lip, but has significant potential in improving the diagnosis of isolated cleft palate.…”
mentioning
confidence: 99%
“…10 The total lip height (a) and greater lip height (b) are measured from points just above the cutaneous roll (the supra-white roll point) at the bow peaks to the height of the ipsilateral philtral column in the lip-columellar crease. The base width of the inferior triangle (c) can then be calculated.…”
mentioning
confidence: 99%